Deep learning approaches to EEG and fMRI data: a comparative study for sleep stage classification - Tanvir, Farhan; Rahman, Tanjilur; Kamal, S M Arfa; Hassan, Mahmudul; Nazia, Nowshin (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.